Tuning planar fault energies of Ni3Al with substitutional alloying: First-principles description for guiding rational alloy design. (1st January 2018) - Kumar, Kaushlendra; Sankarasubramanian, R.; Waghmare, Umesh V.
Abstract: We determine effects of substitutional alloying, at Al or Ni sublattice, with 3d, 4d and 5d series of transition elements on the energies of anti-phase boundary (APB), superlattice intrinsic stacking fault (SISF) and unstable stacking fault (USF) of Ni3 Al using first-principles density functional theoretical calculations. We show that USF and APB energies are maximal for the systems wherein elements having half-filled d-orbitals are substituted at the Al site. Analysis of the data on alloys studied reveals a correlation between SISF and APB energies, which along with d-orbital occupancy can be useful as descriptors in rational design of improved Ni-Al alloys. Graphical abstract: